Workability among migrant diabetic workers: An occupational health-clinic-based study, Kuwait. - Sarah A Bolbol; Shaikhah M Al-Fajjam; Al-Anoud E Al-Ateeq; Shaikha S Al-Hajeri; Salwa F El-Saka (PLOS Global Public Health)
Diabetes Mellitus (DM) can influence physical and mental health, and workability can be affected by how well workers can manage the disease. So, the aim was to assess workability and identify factors associated with decreased workability among migrant diabetic workers. A cross-sectional study was conducted on 134 migrant diabetic workers in an occupational health clinic in Kuwait. Interview questionnaires on sociodemographic, occupational history, and workability index were used. Workers were subjected to clinical examinations and lab tests including alanine transaminase, aspartate aminotransferase, creatinine, fasting blood sugar, and HbA1C. The study showed that among diabetic workers, 19.4% had poor workability, 37.3% had moderate workability, and 34.3% had good to excellent workability. Poor workability was significantly associated with a long history of having DM (≥ 10 years). Workers with poor workability had significantly higher levels of fasting blood sugar (FBS), HbA1c, and creatinine (0.044, 0.019, and <0.001, respectively). Correlation showed that increased level of FBS, HbA1c, and creatinine was significantly associated with decreased levels of workability among diabetic workers (0.04, 0.02, 0.000 respectively). In conclusion, although many adults with diabetes remain productive members of the workforce, effective disease management is essential to minimizing complications and reducing its impact on job performance.